THE EFFECT OF PUBLIC PERCEPTION OF CARBON TRANSACTIONS IN PROMOTING ECONOMIC PROSPERITY: A SHARIA ECONOMIC APPROACH - Zaenafi Ariani; Malami Muhammad Garba (Universitas Sains Al Qur'an, 2026)
This study aims to analyse public perception of carbon transactions in relation to improving economic welfare through sharia economic approach, as well as to examine the role of sharia banking and financial technology (fintech) as facilitators of sustainable carbon trading in accordance with sharia principles. The method used is mixed methods with sequential explanatory design. Quantitative data collection through a survey approach using a Likert-scale questionnaire with a total of 20 questions. This instrument is designed to measure the level of understanding, economic impact, and conformity of carbon transaction practices with sharia economic values. Respondents were purposively selected to represent individuals who have knowledge or involvement in related issues totalling 51 respondents. Quantitative data analysis was followed by a qualitative approach through observation and in-depth interviews with academics, industry players and sharia economic figures to gain a contextual understanding of the survey results. The findings show that public understanding of the concept and mechanism of carbon trading from a sharia perspective is still limited. Although some people show concern for environmental issues, in-depth knowledge about carbon trading is still minimal. However, respondents who understand sharia principles argue that carbon transactions can be justified as long as they fulfil the principles of fairness, transparency and are free from uncertainty (gharar).